Lidamycin inhibits tumor initiating cells of hepatocellular carcinoma Huh7 through GSK3β/β‐catenin pathway. Issue 1 (16th July 2013) - Chen, Yi; Yu, Dongke; Zhang, Caixia; Shang, Boyang; He, Hongwei; Chen, Jinjing; Zhang, Hao; Zhao, Wuli; Wang, Zhen; Xu, Xiaoyu; Zhen, Yongsu; Shao, Rong‐guang
Abstract Recently, tumor initiating cells are considered as the central role of tumorigenicity in hepatocellular carcinoma. Enediyne anticancer antibiotic lidamycin with great potential antitumor activity is currently evaluated in Phase II clinical trials. In this study, we evaluated the effect of lidamycin on tumor initiating cells of hepatocellular carcinoma Huh7 and identified the potential mechanism. Flow cytometry analysis and sorting assay, surface marker assay, sphere formation assay, and aldefluor assay were used to evaluate the effect of lidamycin on Huh7 tumor initiating cells in vitro. To investigate the potential mechanism, the activity of GSK3β/β‐catenin pathway was detected by Western blot and T cell factors transcriptional activity assay. Subcutaneous tumor model in nude mice was used to observe in vivo effect of lidamycin on Huh7 cells. Lidamycin decreased the proportion of EpCAM+ cells and the expression of EpCAM protein. Lidamycin inhibited sphere formation of sorted EpCAM+ cells in 7 d, and of parental cells in three serial passages. The population of aldehyde dehydrogenase‐positive cells was reduced by lidamycin. In addition, lidamycin restrained tumor volume and incidence in vivo. Lidamycin activated GSK3β, and degraded the activity of β‐catenin. Consequently, transcriptional activity of β‐catenin/T cell factors was decreased. In brief, these results suggest that lidamycin suppressed Huh7 tumor initiating cells via GSK3β/β‐catenin pathway. These findings reveal the potential mechanism of lidamycin on tumor initiating cells and the benefit for further clinical evaluation. © 2013 Wiley Periodicals, Inc.